Identification of genes involved in the segregation of yeast 2 micron plasmid - Annie Albert Demin (2009)
The 2 μ plasmid of Saccharomyces cerevisiae is a circular, stable, high-copy-number, extrachromosomal “selfish” DNA element without any selective advantage to its host. In addition to the plasmid-encoded stability system, consisting of the Rep1 and Rep2 proteins and the STB DNA, chromosome-encoded proteins that affect the fidelity of chromosome segregation were also found to affect plasmid segregation in a similar way. Seven genes that were previously reported to be involved in chromosome stability were investigated by gene disruption. Phenotypes produced by gene disruption may provide important clues for the gene function. Disruption fragments for HOS1 , RME1 , HHT2, RPA34 , HHF2, CIN8 and EGD1 genes were generated by PCR amplification of the KanMX4 G418-resistance module. The resulting PCR fragments were transformed into GY59 strain already bearing pS-ADE1 plasmid which is identical to wild-type 2 μ plasmid except for the ADE1 insertion and therefore served as an indicator of plasmid loss in yeast strain by accumulation of red pigment. Disruption of these genes caused no significant effect on the 2 μ plasmid stability which was indicated by the formation of white colonies. pAFS60 carrying STB sequence was localised in mutant cells by fusing green fluorescent protein (GFP) to a DNA binding protein (lac repressor) on pAFS135 and incorporating binding sites (lac operator) for the GFP-lac repressor fusion protein on the pAFS60. In the presence of 2 μ plasmid (pS-ADE1 ), artificial plasmid (pAFS60) carrying the STB sequence can be stably maintained utilising Rep1 and Rep2 in trans at high copy number, although with less stability and at lower copy number than 2 μ plasmid. In conclusion, HOS1 , RME1 , HHT2, RPA34 , HHF2 , CIN8 and EGD1 genes are not involved the 2 μ plasmid stability.